The pathways to tumor suppression via route p38 - Han, Jiahuai; Sun, Peiqing (Trends in biochemical sciences (Amsterdam. Regular ed.), 2007)
Besides its well-known functions in inflammation and other stresses, the p38 mitogen-activated protein kinase pathway also negatively regulates cell proliferation and tumorigenesis. Inactivation of the p38 pathway enhances cellular transformation and renders mice prone to tumor development with concurrent disruption of the induction of senescence. Conversely, persistent activation of p38 inhibits tumorigenesis. Mechanistic insights into this additional p38 function are starting to emerge. For example, p38 has been shown to have a crucial role in oncogene-induced senescence, replicative senescence, DNA-damage responses and contact-inhibition. In addition, the role of the p38 pathway in proliferative control and tumor suppression is mediated by its impact on several cell-cycle regulators. These findings reveal a tumor-suppressing function of the p38 pathway, and indicate that components of the p38 pathway are potential targets for novel cancer therapies.